Human oligodendrocytes from embryonic stem cells: conserved SHH signaling networks and divergent FGF effects - Hu, Bao-Yang (Company of Biologists, 2009)
Human embryonic stem cells (hESCs) offer a platform to bridge what we have learned from animal studies to human biology. Using oligodendrocyte differentiation as a model system, we show that sonic hedgehog (SHH)-dependent sequential activation of the transcription factors OLIG2, NKX2.2 and SOX10 is required for sequential specification of ventral spinal OLIG2-expressing progenitors, pre-oligodendrocyte precursor cells (pre-OPCs) and OPCs from hESC-derived neuroepithelia, indicating that a conserved transcriptional network underlies OPC specification in human as in other vertebrates. However, the transition from pre-OPCs to OPCs is protracted. FGF2, which promotes mouse OPC generation, inhibits the transition of pre-OPCs to OPCs by repressing SHH-dependent co-expression of OLIG2 and NKX2.2. Thus, despite the conservation of a similar transcriptional network across vertebrates, human stem/progenitor cells may respond differently to those of other vertebrates to certain extrinsic factors.